Meningkatkan Minat Baca Anak-anak Melalui Cerita Rakyat Lokal: Program Dongeng dan Kreativitas Untuk Membuka Dunia Imajinasi - Novia, Lisa; Firdausi, Isha Ananda; Darmawan Putri, Salwa Rulla; Fitri, Silhana; Hamzah, Yusuf; Srihayani (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The low interest in reading and the declining attention toward local folklore among early childhood children pose a serious challenge to cultural resilience and national literacy quality. This Community Service (PKM) activity aims to increase reading interest and stimulate the imagination of children at PAUD Glora Hati, Pondok Aren, through a storytelling and creativity program. The implementation method utilized an edutainment approach that combines storytelling techniques using hand puppet media with interactive letter-arrangement games. The stages of the activity included orientation, delivery of the "The Mouse and the Lion" fable, Q&A sessions, group games, and providing appreciation. The results of the service showed an increase in children's enthusiasm and active participation in the literacy process. Through the use of hand puppets, children were able to understand the plot and internalize moral values more effectively. Furthermore, the letter-arrangement game proved to enhance children's cognitive abilities in recognizing the alphabet and collaborating within a team. The conclusion of this activity confirms that the learning-through-play method is the most effective strategy for introducing literature to early childhood. This program not only improves language skills but also expands children's imaginative worlds and provides new insights for teachers in developing varied learning media. It is suggested that schools continue to integrate local folklore into the daily curriculum to maintain the sustainability of students' reading interest.